Nonlinear aeroelastic modeling and comparative studies of three degree of freedom wing-based systems - Bouma, A. (2023)
The effects of structural and aerodynamic nonlinearities are investigated on an aeroelastic system with three degrees of freedom, those being plunge, pitch, and flap motions using two different aerodynamic load representations. Stall effects are introduced using quasi-steady and unsteady aerodynamic representations. The effects of the unsteadiness of the flow and stall effects on the type of Hopf bifurcation and the limit cycle oscillations of the system are explored. A comparative study between the unsteady and quasi-steady representations from a nonlinear perspective is also carried out. Results from the linear analysis show that for this specific aeroelastic system, its linear characteristics are dependent on the aerodynamic representation and the system's design. Additionally, the quasi-steady approximation of the aerodynamic loads results in an inaccurate prediction of the linear flutter speed. Furthermore, the nonlinear analysis shows the existence of an instability shift from the supercritical to the subcritical type, depending on the value of the stall coefficient, as well as that of the cubic nonlinearities, and is more dominantly for the case when the quasi-steady representation is considered. Results show that, even for small reduced frequencies and small angles of attack scenarios, the unsteady representation of aerodynamic loads is critical to correctly predict the flutter speed, instability type, and system's dynamics.